I IMPLEMENTASI PENDAMPINGAN FASILITATOR PENDAMPING ACCESS TO KNOWLEDGE REMOTE SITE DI MOBILE MARKETING SYARI'AH JOGOROTO DALAM PERSPEKTIF HUKUM EKONOMI SYARI'AH: IMPLEMENTATION OF ACCESS TO KNOWLEDGE REMOTE SITE ACCESS TO KNOWLEDGE FACILITATOR ASSISTANCE IN MOBILE MARKETING SYARI'AH JOGOROTO FROM A SYARI'AH ECONOMIC LEGAL PERSPECTIVE - Sherli Israni; Faruq, Ahmad (Program Studi Hukum Ekonomi Syariah, Universitas Hasyim Asy'ari, 2024)
This article discusses the Implementation of Assistance for Remote Site Access To Knowledge Assistance Facilitators in Mobile Marketing Syari'ah Jogoroto in the Perspective of Sharia Economic Law. This research uses an empirical juridical approach method, this approach is based on a reality that occurs as a reality in society. Data collection through field observation, interviews, and questionnaires. The data obtained are processed descriptively and analyzed using the perspective of Sharia Economic Law. The results of this study show that the implementation after this assistance 60.47% of MSME customers developed because they implemented well the presentation of assistance and carried out all the principles of shari'ah Amanah, benefit, ash-Siddiq. 23% and 4.95% of MSME customers are stuck and regressed because they only implement one shari'ah principle. And there are 13.95% who went out of business because they did not implement the assistance provided and did not implement any shari'ah principles.